Nonlinear dynamic dnalysis of high speed rolling element bearings due to cage run-out - Harsha, S. P.; Kankar, P. K.; Purohit, R. K. (Computer Assisted Methods in Engineering and Science, 2022)
The paper presents an analytical model to investigate the nonlinear dynamic behavior of rotor bearing system due to cage run-out. Due to run-out of the cage, the rolling elements no longer stay equally spaced. The mathematical model takes into account the sources of nonlinearity such as Hertzian contact force and cage run-out, resulting transition from no contact-to-contact state between rolling elements and races. The contact between the rolling elements and races is treated as nonlinear springs. The nonlinear stiffness is obtained by application of Hertzian contact deformation theory. The implicit type numerical integration technique Newmark-β with Newton Raphson method is used to solve the nonlinear differential equations iteratively. The results are presented in the form of Fast Fourier Transformations (FFT) and contact force-time responses. It is implied from the obtained FFT that due to the cage run-out, the ball passage frequency is modulated with the cage frequency.